Hindutva as a variant of right-wing extremism - Leidig, Eviane (Patterns of prejudice, 2020)
Leidig's article addresses a theoretical and empirical lacuna by analysing Hindutva using the terminology of right-wing extremism. It situates the origins of Hindutva in colonial India where it emerged through sustained interaction with ideologues in Fascist Italy and Nazi Germany who, in turn, engaged with Hindutva to further their own ideological developments. Following India's independence, Hindutva actors played a central role in the violence of nation-building and in creating a majoritarian identity. Yet Hindutva was not truly 'mainstreamed' until the election of the current prime minister, Narendra Modi, in 2014. In order to construct a narrative that furthered Hindu insecurity, Modi mobilized his campaign by appealing to recurring themes of a Muslim 'threat' to the Hindu majority. The result is that Hindutva has become synonymous with Indian nationalism. Leidig seeks to bridge the scholarly divide between, on the one hand, the study of right-wing extremism as a field dominated by western scholars and disciplines and, on the other, the study of Hindutva as a field that is of interest almost exclusively to scholars in South Asian studies. It provides an analytical contribution towards the conceptualization of right-wing extremism as a global phenomenon.